2023
DOI: 10.1002/smll.202301975
|View full text |Cite
|
Sign up to set email alerts
|

Edge Graphitized Oxygen‐Rich Carbon Based on Stainless Steel‐Assisted High‐energy Ball Milling for High‐Capacity and Ultrafast Sodium Storage

Abstract: Oxygen doping is an effective strategy for constructing high‐performance carbon anodes in Na ion batteries; however, current oxygen‐doped carbons always exhibit low doping levels and high‐defect surfaces, resulting in limited capacity improvement and low initial Coulombic efficiency (ICE). Herein, a stainless steel‐assisted high‐energy ball milling is exploited to achieve high‐level oxygen doping (19.33%) in the carbon framework. The doped oxygen atoms exist dominantly in the form of carbon‐oxygen double bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…[16] The refined spectra of Na 1s for HC and DP‐HC are shown in Figure 3l. A single peak situated at 1072.5 eV is the characteristic peak of Na 2 O [8a,17] . Therefore, the SEI components of DP‐HC are mainly contributed by Na 2 CO 3 , NaF and Na 2 O.…”
Section: Resultsmentioning
confidence: 96%
“…[16] The refined spectra of Na 1s for HC and DP‐HC are shown in Figure 3l. A single peak situated at 1072.5 eV is the characteristic peak of Na 2 O [8a,17] . Therefore, the SEI components of DP‐HC are mainly contributed by Na 2 CO 3 , NaF and Na 2 O.…”
Section: Resultsmentioning
confidence: 96%
“…CFG and CFG-S exhibit low ICEs of 65.5 and 62.3%, respectively, close to those of most other pristine or heteroatom-doped carbon anodes with a heating treatment temperature of <1000 °C. However, CFG-S-M exhibits a very high ICE of 91.2%, which is rarely achieved in the S-doped carbon anode and comparable to those of most other carbon anodes that exhibit outstanding ICE values because they underwent complicated surface modification or presodiation technologies. , …”
Section: Resultsmentioning
confidence: 96%
“…Heteroatom doping is a useful strategy to modify carbon anodes and solve their current shortcomings. As one of the commonly used doping atoms (e.g., O, N, S, and P), S doping considerably promotes sodium storage. On the one hand, S can form Na 2 S x compounds via redox reactions with Na + , contributing numerous sodium storage sites along with high capacity. On the other hand, the large atomic radius of S increases the layer spacing in carbon materials after S doping, promoting the intercalation of Na + into the carbon structure.…”
Section: Introductionmentioning
confidence: 99%
“…4f). Several nanocarbons based on surface and/or bulk chemisorption mechanisms show reversible capacities of 120–380 mA h g −1 and high voltage of 1.0–1.6 V. 53–71 In the case of hard carbons, higher reversible capacities of 220–480 mA h g −1 and lower average voltage ranges of 0.2–0.6 V were achieved. 15–17,19,20,22–34,47–52 The PHC-series samples in this study also showed reversible capacities and voltages similar to those of previously reported hard carbon materials.…”
Section: Resultsmentioning
confidence: 99%